AN ONLINE SELF-MANAGEMENT PROGRAM FOR CHRONIC PAIN: PACT—PATIENT ACTIVATED CARE AND TRAINING. (11th November 2018) - Whitebird, R; Fricton, J; Vazquez-Benitez, G; Grossman, E; Ziegenfuss, J; Lawson, K
Abstract: Pain related to temporomandibular disorders (TMD) can be a challenge for many people resulting in headaches, jaw pain, depression, chronic pain, anxiety, and disability. We conducted a pilot randomized controlled trial of a Patient-Activated Care and Training (PACT) program that uses online education and self-management training with telehealth coaching to help people self-manage their TMD pain. We recruited 81 people with TMD pain and randomized them to either the PACT Program (n=40) or Traditional Self Care (TSC; n=41). Participants in PACT engaged in 8 modules focused on understanding pain, reducing risk factors, and enhancing protective factors. Survey measures were obtained at baseline, 8 and 16 weeks. Cohen's -d statistic was estimated for survey outcomes and a subset of participants were interviewed regarding their experience in the program. Participants had a mean age of 46 (PACT), 49 (TSC) and the majority were white and female. Outcomes at 16 weeks showed improvement in the PACT group relative to TSC on measures of pain severity (PACT: 1.22, TSC: -.74), pain interference in daily living (PACT: -.49, TSC: -.27), and chronic pain self-efficacy (PACT: .45, TSC: .27). In study interviews, participants focused on how they learned to make sustainable changes in their daily life, manage their pain, and learned how many aspects of their life affect their experience of pain. Clinically meaningful effects were observed suggesting that the PACT Program may offer an accessible online approach to the self-management of chronic TMD pain, providing support for the need of a full clinical trial.